ANALISIS PEMIKIRAN SYEKH YASIN AL-FADANI TENTANG HISAB RUKYAT TRADISIONAL - Sinta; Halimah B; Akmal, Andi Muhammad (HISABUNA: Jurnal Ilmu Falak, 2023)
Hisab rukyat is an absolute problem in the field of astronomy. In this research on reckoning rukyat, the author refers to Sheikh Yasin al-Fadani’s thought of reckoning rukyat in Kitab al-Mukhtasor al-Muhadzab fi Ihtiroji al-Awqat wa al-Qiblah bi ar-Rubi’ al-Mujib, with the research approach used is the syar’i astronomy and character approach, in this case Sheikh Yasin al-Fadani. From the results of the study, the authors found that Syekh Yasin al-Fadani’s astronomical scientific Sanad was the highest sanad obtained from several of his teachers, both from those in the Middle East and from the Archipelago. That is, Sheikh Yasin al-Fadani is connected with his astronomical scientific chain with a number of scholars in the world and in the archipelago. Regarding the problem of Sheikh Yasin al-Fadani’s rukyat reckoning thought which is still fairly classic, such as the use of Rubu ’Mujayab, it is not much different from the rukyat reckoning system in today’s era. So it can be said that Sheikh Yasin al-Fadani’s rukyat reckoning thinking is in line with what is in the astronomy literature today, both in the calculation system for the beginning of prayer times, Qibla direction, calendar and in determining the beginning of the month. Keywords: Hisab Rukyat, Rubu’ Mujayab, Sheikh Yasin al-Fadani